Promoting the scaling of innovations and strengthening technical capacities in Pueblo Nuevo, Córdoba - Rendon, Natali; Guerrero, Crhistian (2025)
In September 2025, a training and technical support plan was implemented in the municipality of Pueblo Nuevo, Córdoba, aimed at strengthening the capacities of local producers and technicians and promoting the adoption of agricultural innovations, with an emphasis on biofortified maize and rice crops. The initiative benefited 58 farmers and 15 technicians from the Municipal Mayor’s Office and focused on improving planting, agronomic management, and post-harvest practices, thereby contributing to food and nutritional security in the territory.